Overview and Recent Advances of Regulatory T cell Therapy in Solid Organ Transplantation (Iranian Journal of Kidney Diseases, 2021)
Solid organ transplant recipients are in high demand for developed immune-modulating agents to control allo-immune responses following transplantation. The immunosuppressive agents offer the recipients improved short-term graft survival; nonetheless, this benefit is tempered by unavoidable long-term adverse events of these medications. Active control of allo-response using therapeutic cell transfer has gained much attraction during the last few years. It is widely established that regulatory T cells (Tregs) control immune responsiveness to allo-antigens and contribute to the induction of tolerance. Here, it is aimed to review recent results regarding Tregs and chimeric antigen receptor (CAR) Tregs therapy in solid organ transplantation and discuss strategies to overcome technical challenges of developing successful Tregs/CAR Tregs therapy.